2005
DOI: 10.1002/hep.20710
|View full text |Cite
|
Sign up to set email alerts
|

An intronic silencer element is responsible for specific zonal expression of glutamine synthetase in the rat liver†

Abstract: The most striking phenomenon of glutamine synthetase (GS) expression in the liver is its unique restriction to cells surrounding the terminal hepatic venules. Expression is positively regulated by elements located in the 5 -upstream region and in the first intron of the gene. It was long believed that transcription factors present in GS-positive cells and absent in GSnegative cells are responsible for the phenomenon of zonal expression. However, strong enhancers are equally active in both types of cells. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…In fact, experimental evidence exists in favor of the idea of a silencing effect mediated by Ras proteins from published data: (i) expression of an activated version of Ha-ras in mammary carcinoma cells and in keratinocytes has been demonstrated to down-regulate AhR function and expression of CYP1A1 31 ; (ii) most GS-negative tumors from acutely PB-induced mice do not respond with expression of CYPs of family 2 as do their GS-positive counterparts 12 ; (iii) PB-induction of responsive CYPs in isolated hepatocytes requires serum-free medium, which is likely attributable to the presence of growth factors such as epidermal growth factor in serum, which are known to activate Rasdependent signaling and also suppress expression of CYP1A1 32 as well as CYP2B1 and CYP3A1. 33 Very recently, a silencer element within intron 1 of GS was shown to mediate negative regulation of gene expression in periportally located hepatocytes, 34 which could be subject to regulation by a Ras-dependent signal. This hypothesis contrasts results obtained in other systems: for example, Ras and ␤-catenin were found to cooperate in activation of the cyclin D1 promoter, 35 and transcription of an artificial ␤-catenin/TCF-dependent reporter was stimulated by insulin and insulin-like growth factor-1, requiring activation of Ras.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, experimental evidence exists in favor of the idea of a silencing effect mediated by Ras proteins from published data: (i) expression of an activated version of Ha-ras in mammary carcinoma cells and in keratinocytes has been demonstrated to down-regulate AhR function and expression of CYP1A1 31 ; (ii) most GS-negative tumors from acutely PB-induced mice do not respond with expression of CYPs of family 2 as do their GS-positive counterparts 12 ; (iii) PB-induction of responsive CYPs in isolated hepatocytes requires serum-free medium, which is likely attributable to the presence of growth factors such as epidermal growth factor in serum, which are known to activate Rasdependent signaling and also suppress expression of CYP1A1 32 as well as CYP2B1 and CYP3A1. 33 Very recently, a silencer element within intron 1 of GS was shown to mediate negative regulation of gene expression in periportally located hepatocytes, 34 which could be subject to regulation by a Ras-dependent signal. This hypothesis contrasts results obtained in other systems: for example, Ras and ␤-catenin were found to cooperate in activation of the cyclin D1 promoter, 35 and transcription of an artificial ␤-catenin/TCF-dependent reporter was stimulated by insulin and insulin-like growth factor-1, requiring activation of Ras.…”
Section: Discussionmentioning
confidence: 99%
“…Little Ccn2/Ctgf promoter activity was found in HNF4 α + hepatocytes located at periportal and pericentral areas during DDC-induced liver injury as shown in Figure 2(b) and Supplemental Figure  1. These observations were further supported by immunofluorescent staining for glutamine synthetase, an enzyme specifically expressed in hepatocytes around zone 3 of the liver acinus in the livers [31]. Lastly, absence of Ccn2/Ctgf promoter activity was found in mesenchymal cells that expressed vimentin (Supplemental Figure  3), implying that CCN2/CTGF was not directly involved in epithelial-mesenchymal transition during DDC-induced liver injury in mice.…”
Section: Resultsmentioning
confidence: 74%
“…This is in fact not surprising, since we have shown that expression of endogenous GS is pre-vented by a factor that binds to an element located within the first intron. 2 This element is not present in the reporter genes used in the present work.…”
Section: Discussionmentioning
confidence: 94%
“…Only recently, a silencer located within the first intron of the gene was shown to be able to restrict expression to the GS-positive population. 2 However, the high level of expression, its developmental profile, as well as the factors and signal transduction pathways involved in positive regulation remain enigmatic. On the other hand, recent experiments point toward a role of the canonical wnt-signaling pathway mediated by ␤-catenin during development, 3 in the adult liver 4 as well as in tumorigenesis.…”
mentioning
confidence: 99%